2012
DOI: 10.4081/idr.2012.3853
|View full text |Cite
|
Sign up to set email alerts
|

Human immunodeficiency virus and its effects on the visual system

Abstract: During the first 15 years of the AIDS epidemic patients experienced a high incidence of blindness due to cytomegalovirus (CMV) retinitis and other severe ocular opportunistic infections. Highly active anti-retroviral therapy, introduced in 1996, dramatically decreased the incidence of CMV retinitis. Though CMV retinitis still causes 40% of vision loss in AIDS

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 94 publications
0
5
0
Order By: Relevance
“…119 Occlusion of the central retinal vein happens in 0.64% of AIDS patients. 120 Dunn et al 121 reported that occlusion of the retinal vein was observed in 38 eyes of 33 (1.3%) of the 2484 patients. Furthermore, HIV patients have a low chance to develop occlusion of the retinal vein, however, visual loss and complications are more general in patients with HIV.…”
Section: Occlusion Of Retinal Veinmentioning
confidence: 99%
See 1 more Smart Citation
“…119 Occlusion of the central retinal vein happens in 0.64% of AIDS patients. 120 Dunn et al 121 reported that occlusion of the retinal vein was observed in 38 eyes of 33 (1.3%) of the 2484 patients. Furthermore, HIV patients have a low chance to develop occlusion of the retinal vein, however, visual loss and complications are more general in patients with HIV.…”
Section: Occlusion Of Retinal Veinmentioning
confidence: 99%
“…Venous occlusions and retinal arterial in patients with HIV are commonly correlated with lymphoproliferative disorders and CMV retinitis 119 . Occlusion of the central retinal vein happens in 0.64% of AIDS patients 120 . Dunn et al 121 reported that occlusion of the retinal vein was observed in 38 eyes of 33 (1.3%) of the 2484 patients.…”
Section: Occlusion Of Retinal Veinmentioning
confidence: 99%
“…Human immunodeficiency virus has been isolated from tears, contact lenses, aqueous, vitreous and ocular tissues [22][23][24][25][26] but there is no evidence of transmission through these. Infection requires direct contact between blood/ body fluids and mucous membranes or damaged skin, for example, through (unprotected) sexual contact or through sharing needles and/or syringes with an infected person, through receiving blood transfusions, blood products or organ/tissue transplants that are contaminated with HIV.…”
Section: Human Immunodeficiency Virus/ Acquired Immune Deficiency Synmentioning
confidence: 99%
“…These systemic diseases include sarcoidosis,10 11 tuberculosis,12 Vogt–Koyanagi–Harada (VKH) syndrome,13 rheumatological disorders such as systemic lupus erythematosus,14 Sjogren syndrome,15 and neuro-Behcet,16 as well as systemic viral infections such as cytomegalovirus (CMV),17 18 HIV19 and Epstein–Barr virus (EBV) 20–23. One or both eyes may be involved.…”
Section: Aetiologiesmentioning
confidence: 99%